Gender equality considerations when caregivers interface with SASSA - Van Vrede, Brenton Ian (My University, 2015)
The Child Support Grant (CSG) is one of the largest programmes in government affecting the lives of more than 11 million children and 5.8 million caregivers, who are mainly women. Even though the CSG programme does not explicitly target women, over R44 billion a year is transferred to women for children. The primary implementing agency for the CSG is the South African Social Security Agency’s (SASSA). This research measures the knowledge, attitude and behaviour of the SASSA operational staff, and infers its effect on gender equality. A survey was conducted with a random sample of 112 operational staff members from SASSA. The survey uncovered bad behaviour from research respondents such as being rude; making insulting remarks; gossiping; and swearing at caregivers. Stigmatised attitudes with regards to dependency, deviant behaviour and pregnancy were found to be prevalent. The research concludes that exposing women to stigma and abusive behaviour while they are serving as voluntary delivery agents for a government programme, is tantamount to exploitation; and widens the gender gap. Keywords: gender equality, child support grant, CSG, SASSA.
MM
Keywords: Social security, Child caregivers, Caregivers, Sex discrimination against women -- South Africa.